Design and simulations of analog circuit using LTspice - Lim, Jason Yong Soon (Nanyang Technological University, 2021)
Today, newer circuit simulation programs have in-built graphical user interfaces (GUI) that aid the readability and operability of these circuit simulators. For instance, universal component symbols (i.e., resistors are represented with zig-zag lines, capacitors are represented with a double line, etc.) are used in the interface which makes it more intuitive to use as compared to early simulation programs like FORTRAN. [1] There are many circuit simulators used in industries to date, however, the modern circuit simulator of interest in this paper is LTspiceXVII. LTspice is a sophisticated SPICE-based Analog electronic simulation software, developed by Linear Technology, which provides a platform for users to draft, test, compare, evaluate, and refine the circuit design before physical prototyping. As compared to other SPICE simulators, LTspice allows users to view the theoretical results fast and this allows the user the luxury of time to iterate and optimise their design. [2] This report aims to document and understand the process of simulating and optimizing a single input to differential output amplifier with the use of a LTspice simulator.